Próby leksykografii religijnej w zasobach polskiego Internetu - Czarnecka, Katarzyna (Poznańskie Spotkania Językoznawcze, 2015)
Research material analyzed in the article includes dictionaries devoted to religious contents available on Polish websites, with particular emphasis on publications related to the Roman Catholic faith (80 items). The aim of the Author is to try to present online religious dictionaries, showing their specificity and related problems. Characteristics include issues such as: 1) thematic scope of dictionaries (domination of the Bible teachings, liturgics and vocabulary typical for specific religious environments and communities); 2) original or secondary nature of the text (online dictionary as an electronic adaptation of a printed work or an independent creation); 3) structure and method of functioning of online dictionaries (text or hypertext; insufficient use of technical possibilities, e.g. connecting entries with a network of links); 4) Choice between a dictionary and an encyclopedia (type of information contained in head entries; alphabetical system typical for a dictionary as a convenient form of conveying any content; a need to study types of definitions); 5) Author’s intentions and stylistic tone of a dictionary (lack of objectivity in conveying information; making comments; persuasiveness in defining meanings, polemics, satire or a joke). Online dictionaries, similarly as most contents published on the Internet, cause problems concerning data reliability. It is also not supported by anonymity and a trend for copying, paraphrasing and moving texts, typical for the Internet.